The Role of Management Information Systems (MIS) in Decision Making - Fitria Eriyanti Putri; Joni Iskandar; Masduki Asbari; Adi Widodo; Riyanto Riyanto (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study is to analyze an information system that is necessary for logical decision-making, so it requires an understanding of the problem and knowledge of alternative solutions. This study report was carried out using a descriptive qualitative method by reviewing scientific articles taken from Google Scholar by taking notes. The results of the study, that more precise information results in better decisions. The quality of information depends on 3 (three) things, namely, the information must be accurate, timely, and relevant. The elements in decision-making that must be considered are the purpose of decision-making, identification of decision alternatives to solve problems, calculations of factors that cannot be known beforehand or are beyond human reach, and the means or tools used to evaluate or measure the result of a decision.